2022
DOI: 10.1097/qad.0000000000003165
|View full text |Cite
|
Sign up to set email alerts
|

Brain aging and cardiovascular factors in HIV: a longitudinal volume and shape MRI study

Abstract: Objective: We aimed to examine the relative contributions of HIV infection, age, and cardiovascular risk factors to subcortical brain atrophy in people with HIV (PWH).Design: Longitudinal observational study.Methods: Virally suppressed PWH with low neuropsychological confounds (n ¼ 75) and demographically matched HIV-negative controls (n ¼ 31) completed baseline and 18-month follow-up MRI scans, neuropsychological evaluation, cardiovascular assessments, and HIV laboratory tests. PWH were evaluated for HIV-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…In summary, we present evidence that peripheral markers of vascular injury are more closely associated with HAND and CNS injury in PWH on suppressive ART than markers of inflammation. Our findings are consistent with the three-hit model proposed by Jakabek et al [20] in which HIV infection, aging, and vascular disease contribute to brain aging in PWH, and suggest that vascular injury markers, particularly VCAM-1, may help to distinguish relative contributions of VCI to HAND. Further studies are warranted to better understand the utility of VCAM-1 and other peripheral markers of vascular injury for identification of HAND biotypes [11,13] and development of tailored interventions in virally suppressed PWH on ART.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In summary, we present evidence that peripheral markers of vascular injury are more closely associated with HAND and CNS injury in PWH on suppressive ART than markers of inflammation. Our findings are consistent with the three-hit model proposed by Jakabek et al [20] in which HIV infection, aging, and vascular disease contribute to brain aging in PWH, and suggest that vascular injury markers, particularly VCAM-1, may help to distinguish relative contributions of VCI to HAND. Further studies are warranted to better understand the utility of VCAM-1 and other peripheral markers of vascular injury for identification of HAND biotypes [11,13] and development of tailored interventions in virally suppressed PWH on ART.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with these findings, cardiovascular risk factors and diagnoses were more prevalent in HAND vs. no HAND and biomarker clustering identified HAND subgroups distinguished by high prevalence of vascular disease and progression to HAD. In the current ART era, HAND frequently has non-HIV-etiologies, with vascular disease being one of the most common [10,[19][20][21]46], and neurocognitive profiles can resemble VCI [10,17,[19][20][21]24,25,46]. Although plasma inflammation markers (e.g., IL-1b, IL-8, IP-10, MCP-1) were increased in PWH, only IL-6 was associated with HAND (particularly MND).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blahak et al suggested that white matter injury can disrupt the prefrontal subcortical motor circuit, resulting in impaired balance and an increased risk of falls (123). In addition to white matter injury, advanced HAND patients may exhibit decreased subcortical volume, caudate nucleus volume, cerebral malacia foci, and brain atrophy (66,124,125). HIV can also contribute to other acute central nervous system diseases, such as stroke.…”
Section: Structural Damage Of Cnsmentioning
confidence: 99%
“…The mechanisms involved in HAND are heterogeneous, including ongoing viral replication in the CNS, neuroinflammation, oxidative stress, vascular disease, blood–brain barrier (BBB) dysfunction, ART-related neurotoxicity, and substance use [ 3 , 4 , 5 ]. Due to persistent inflammation, cerebrovascular disease, and small-vessel disease-related brain injury, PWH are also at increased risk of premature brain aging [ 1 , 6 , 7 , 8 , 9 , 10 ]. However, the relative risk of amnestic mild cognitive impairment (aMCI) and Alzheimer’s disease (AD) in PWH remains unclear [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%